Theology of religions: initial period - Vladimir Shokhin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2025)
The paper deals with such a trend in theology which grows increasingly in the Western world (with the number of publications on and around the topic growing at an exponential rate) but remains almost unfamiliar in Russia. At first, the author offers his conception of its division into periods as based on becoming of the contemporary epoch of theology of religions constituted by elaboration of “the grand triad” of attitudes to other religious tradition from the point of one’s own in the shape of strict differing religious exclusivism, inclusivism and pluralism elaborated by John Hick and introduced in the theological brand under discussion in the 1980s. Correspondingly, the preceding period presented predominantly by German Protestantism is treated as the initial one. This stage is identified by the author as still “Christocentrism”, but the future members of “the grand triad” had its origins already there, and even the polarization of attitudes to non-Christian traditions in the shape of “the radical inclusivism” (Rahner’s conception of “the anonymous Christians”) and “temperate inclusivism” (Althaus and the majority of other Protestant theologians), “exclusivism” (the Barthian position) and such a relativism which is close to “pluralism” (Troeltsch’s line and that of the Second Vatican Council). The author offers also his own considerations concerning the grades of presence of Revelation and resources for salvation in non-Christian religions from the Christian viewpoint.